2022
DOI: 10.1186/s13017-022-00423-1
|View full text |Cite
|
Sign up to set email alerts
|

Timing of pharmacologic venous thromboembolism prophylaxis initiation for trauma patients with nonoperatively managed blunt abdominal solid organ injury: a systematic review and meta-analysis

Abstract: Background Blunt abdominal solid organ injury is common and is often managed nonoperatively. Clinicians must balance risk of both hemorrhage and thrombosis. The optimal timing of pharmacologic venous thromboembolism prophylaxis (VTEp) initiation in this population is unclear. The objective was to evaluate early (< 48 h) compared to late initiation of VTEp in adult trauma patients with blunt abdominal solid organ injury managed nonoperatively. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 45 publications
1
16
0
2
Order By: Relevance
“…Conversely, there were significantly lower odds of VTE when patients received early VTE prophylaxis (OR 0.51; 95% CI 0.33–0.81). In keeping with the results presented by Murphy et al, the most updated meta-analysis [ 40 ] found a non-statistically significant trend toward an increased risk of failure of NOM among patients receiving early VTE prophylaxis (OR 1.76, 95% CI 1.01–3.05), with no significant difference in risk of transfusion. Conversely, odds of DVT were significantly lower in the early group (OR 0.36, 95% CI 0.22–0.59) but without a difference in mortality (OR 1.50, 95% CI 0.82–2.75).…”
Section: Methodssupporting
confidence: 79%
See 2 more Smart Citations
“…Conversely, there were significantly lower odds of VTE when patients received early VTE prophylaxis (OR 0.51; 95% CI 0.33–0.81). In keeping with the results presented by Murphy et al, the most updated meta-analysis [ 40 ] found a non-statistically significant trend toward an increased risk of failure of NOM among patients receiving early VTE prophylaxis (OR 1.76, 95% CI 1.01–3.05), with no significant difference in risk of transfusion. Conversely, odds of DVT were significantly lower in the early group (OR 0.36, 95% CI 0.22–0.59) but without a difference in mortality (OR 1.50, 95% CI 0.82–2.75).…”
Section: Methodssupporting
confidence: 79%
“…The 2017 WSES guidelines stated that LMWH-based prophylactic anticoagulation should be started as soon as possible from splenic trauma, including patients treated with NOM [1]. Our systematic review of the literature regarding this topic retrieved 15 studies, of which two were systematic reviews and meta-analyses [40,41], two were prospective cohort studies [35,38], and 11 were retrospective cohort studies [27,28,36,37,[42][43][44][45][46][47][48]. To date, two systematic reviews and meta-analyses demonstrated that patients undergoing NOM for blunt solid organ injury could be safely and effectively prescribed early VTE prophylaxis.…”
Section: Priority Level: Highmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the published literature delineated above, this clinical and scientific question has triggered sufficient interest and study as to provoke several meta-analyses and systematic reviews 18,19 . The take-home messages of this body of literature are clear.…”
Section: Solid Organ Injuriesmentioning
confidence: 99%
“…In addition to the published literature delineated above, this clinical and scientific question has triggered sufficient interest and study as to provoke several meta-analyses and systematic reviews. 18,19 The take-home messages of this body of literature are clear. Venous thromboembolic event chemoprophylaxis initiation <48 hours of emergency department arrival is associated with a reduction in VTE [8][9][10][11][12][13][14][15] without an increase in failure of nonoperative management [8][9][10][11][12][13][14][15][16][17]19 or need for blood transfusion.…”
Section: Solid Organ Injuriesmentioning
confidence: 99%